Challenges on blue food provision - Morales-Nin, Beatriz; Zimmermann, Fabian; Merino, Gorka; Antelo, Luis T.; Murillas-Maza, Arantxa; Moksness, Erlend (Frontiers in Ocean Sustainability, 2024)
According to the objectives of Frontiers in Ocean Sustainability's Blue Food Provision section, our aim is to contribute to addressing the rising challenges created on marine resources due to global change, unsustainable practices, regulatory barriers, and other constraints. We focus on existing and emerging knowledge, technologies and tools to build capacity and maximize the contribution of marine food systems to food security (i.e., fisheries and aquaculture), nutrition and affordable healthy diets, and social equality, ensuring the achievement of the United Nations Sustainable Development Goals.